MTHFR Gene Polymorphism and Age of Onset of Schizophrenia and Bipolar Disorder - El-Hadidy, Mohamed A. (Hindawi Publishing Corporation, 2014)
Objective. Several studies with contradictory results from different cultures about association of methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism in schizophrenia and bipolar disorders. Little is known about this association in Arab culture and Egypt. So the present study aimed to assess the association of MTHFR C677T polymorphism in bipolar disorder (BD) and schizophrenia in comparison to control group. The association between MTHFR C677T polymorphism and the age at onset in schizophrenia or BD was also studied. Methods. Polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) were used to examine the genotype and allele frequencies of MTHFR C677T polymorphism in 149 healthy subjects and 134 bipolar and 103 schizophrenia patients. Results. In BD and schizophrenia, there was a higher prevalence of MTHFR C677T polymorphism than healthy subjects. Earlier age at onset was found in patients with BD, carrying one copy of the T allele or CT genotypes but not in patients with schizophrenia. Conclusion. The present findings suggest that the MTHFR C677T polymorphisms are likely to be associated with the risk of developing BD and schizophrenia and influence the age at onset of BD but not the age at onset of schizophrenia.